Social Media Application in Agriculture Extension Programming for Small Scale Rural Farmers: Is Knowledge Impeding the Lack of Adoption? - Stephan Moonsammy; Donna Marie Renn Moonsammy (Journal of International Agricultural and Extension Education, 2020)
The purpose of this study was to assess the knowledge level of farmers on basic computer literacy, social media use, and to explore which social and demographic factors affected their knowledge capacity. The study had a final sample of 176 participants from the northern, southern and central regions of Trinidad and Tobago. A survey instrument comprising of 14 multiple-choice questions with one accurate response was developed to decrease bias of farmers randomly selecting the accurate response. The questions addressed knowledge on basic computer and social media literacy. Analysis was conducted using one-way ANOVA with post-hoc testing. Results indicated that there were significant differences in farmers’ performance in the knowledge test based on characteristics such as age, education, and household use of social media and the internet. Based on the findings, minimal training in computer and social media literacy did not impede the farmers’ use of the computer or social media. These discoveries highlight the potential of extension programs using the internet and social media applications to improve communication efficiency among agricultural stakeholders within farming communities.
Keywords: agriculture; computer literacy; Extension; knowledge; social media